Screening of potential GCMS derived antimigraine compound from the leaves of Abrus precatorius Linn to target “calcitonin gene related peptide” receptor using in silico analysis - Parthasarathy V.; Ajay Kumar T.V (Food Science and Human Wellness)
Calcitonin receptor-like receptor (CRLR) is a human protein, that produces a calcitonin gene-related peptide receptor (CGRP) when associates with human receptor activity-modifying protein-1 (HRAMP1). CGRP is believed to be involved in triggering of migraine. Many strategies were employed to design antimigraine drug using various CGRP antagonist/ligands but most of them have failed due to their inability to reach the target “CGRP receptor” as they get metabolized before conferring their pharmacological action and exhibit toxic effect to the liver. The present study, evaluated the binding of 13 phyto-chemical compounds of “Abrus precatorius” identified through GCMS analysis against the protein CGRP using “Discovery Studio software”. The molecular docking study and ADME/T properties prediction were performed with the compounds using C-DOCKER module. The results showed that five lead compounds of A. precatorius may act as good inhibitors for migraine headache and the compounds can be re-designed and synthesized for better antimigraine activity. Keywords: Calcitonin gene-related peptide, Abrus precatorius Linn, Discovery studio, Migraine, C-DOCKER, ADME properties